Design of gelatin biodegradable nano particles as a carrier system for hydrophilic macromolecules/proteins using nano precipitation technique: A resourceful approach for drug delivery - Abdel-Mageed, Heidi Mohamed (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The objective of this study was to design and optimize formulation of biodegradable and biocompatible gelatin nano particle (GNP) using nano-preciptation technique, as potential delivery systems for hydrophilic macromolecules/proteins using bovine serum albumin (BSA) as a model drug. Various parameters were studied, including the concentration of stabilizer, concentration of gelatin, effect of non-solvent nature and the solvent/non-solvent volume ratio. The robustness of the modified methodology was investigated and the prepared GNP was characterized with respect to particle size, PDI using Zetasizer and morphology using Scanning Electron Microscope (SEM). Results showed that among the tested surfactants, poloxamers were able to stabilize the GNP with a minimum concentration of 7% to prepare stable nano particles in the size range 180–240 nm. n-butanol, ethyl ether, acetone and acetonitrile did not allow GNP formation, while on using methanol and ethanol, stable GNP was produced. Increasing the polymer concentration above 25mg/ml greatly increased medium viscosity and caused agglomeration. An optimized formulation (20 mg/ml gelatin, 2% BSA, 7% poloxamer 407 and using ethanol as non-solvent) was prepared with 88% entrapment efficiency (EE %). SEM images showed spherical GNP where, loading BSA did not affect GNP morphology. The cumulative release of BSA after 72 hours was equivalent to 80%. Storage study indicated physical stability GNP after storage at different temperatures for 60 days. The results presented in this study demonstrate and highlight the unexplored potentials of the nano precipitation method for the preparation of nano particles from hydrophilic gelatin polymer for sustained delivery of protein drugs.